2013
DOI: 10.3189/2013jog12j056
|View full text |Cite
|
Sign up to set email alerts
|

Ice flow velocities over Vostok Subglacial Lake, East Antarctica, determined by 10 years of GNSS observations

Abstract: ABSTRACT. Repeated Global Navigation Satellite Systems (GNSS) observations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 33 publications
7
26
3
Order By: Relevance
“…The first type are observations performed on lightweight snowmobiles. With the help of such profiles Richter et al (2014a) have shown that the surface elevation around Vostok Station has been stable over the last decade, confirming the results of permanent GNSS observations (Richter et al, 2008(Richter et al, , 2014a. Such profiles acquired on snowmobiles provide accuracies of only a few centimetres (see also King et al, 2009;Siegfried et al, 2011) and are thus well suited for precise studies on local elevation and elevation changes.…”
Section: Kinematic Gnss Observationssupporting
confidence: 72%
“…The first type are observations performed on lightweight snowmobiles. With the help of such profiles Richter et al (2014a) have shown that the surface elevation around Vostok Station has been stable over the last decade, confirming the results of permanent GNSS observations (Richter et al, 2008(Richter et al, , 2014a. Such profiles acquired on snowmobiles provide accuracies of only a few centimetres (see also King et al, 2009;Siegfried et al, 2011) and are thus well suited for precise studies on local elevation and elevation changes.…”
Section: Kinematic Gnss Observationssupporting
confidence: 72%
“…These might form subglacial lakes, analogous to terrestrial lakes such as Vostok in Antarctica (Siegert and Rigley, 1998;Siegert et al, 2001;Kwok et al, 2000;Bell et al, 2002;Studinger et al, 2004;Richter et al, 2013), that would infill with sediment, perhaps contributing to the explanation for the shallow, degraded character of Noachian highland craters (Craddock and Maxwell, 1993;Craddock et al, 1997;Craddock and Howard, 2002;Weiss and Head, 2014). We conclude that the Late Noachian icy highlands are unlikely to have ever had widespread wet bed conditions, although the presence of limited "lakes" in deep craters is a possibility given a supply limit of 4 5X.…”
Section: Results: Discussionmentioning
confidence: 90%
“…The abundance of subglacial water bodies underneath this portion of the ISIS may have considerably increased basal ice‐flow velocity (Bell, ). It has been demonstrated that subglacial lakes in Antarctica and development of subglacial meltwater drainage in Greenland control the increase in ice stream velocities (Shepherd et al ., ; Richter et al ., ). This relation implies that the retreat of the ISIS during deglaciation, illustrated by the deposition of proglacial sediments above subglacial sediments in Ballyhorsey and Killiney Bay, occurred in response to and along with high ice‐flow velocity (Rijsdijk et al ., ; Clerc et al ., ).…”
Section: Discussionmentioning
confidence: 99%